Silence and poetic inwardness in the writings of David Malouf (Journal of the Association for the Study of Australian Literature, 2014)
James Tulip's argument that David Malouf's ‘achievement is essentially that of a poet’ seems cogent, not only because of Malouf's lifelong commitment to poetry but because his novellas (and at least sections of his novels) might be read as long prose poems. These novellas do contain narratives but they are not driven by narrative. Nor are they most notable in the Modernist way as character studies; the novellas' characters do not engage in extensive social interaction. Rather, as individuals they engage in ideas, in existential contemplations of the self meeting a rich but complex universe. Dante always seems very separate from Johnno; Ovid is in exile; the terrorist in 'Child's Play' hardly talks to his colleagues. In fact, in their climaxes the main characters turn away from the possibilities of social interaction to achieve a state of equanimity in silence: the terrorist walking under apple blossom, Ovid as he steps into ‘clear sunlight’, Carney cleansing himself in the stream and Adair eating bread in an ‘outpouring’ of early morning light. In this retreat they resemble to some extent Horace on his Sabine farm, Montaigne on his Bordeaux estate, and Voltaire at Ferney – the tradition that Malouf describes in his essay on ‘The Happy Life’. Malouf's characters may be seen in opposition to contemporary society's ‘fear of inactivity, of stillness; most of all of the withdrawal of every form of chatter or noise in an extended and unendurable silence’. Adair wonders whether ‘what we are really committed to in our hearts is an unceasing motion’. It is poets who have found value in silence and recollections of tranquillity; Keats's sweeter ‘unheard music’ represented a silence that was a kind of perfection, not just the absence of noise, and the French Symbolistes were intent on finding it. Malouf's characters differ from Horace, Montaigne and Voltaire in that they stumble on silence or have it thrust upon them. However, this does not reduce the meaningfulness of the silence they experience. Malouf is neither a classical figure, a Renaissance humanist, nor a man of the Englightenment, although his writing evinces some empathy with all three. He is a modern figure who thinks our world and us ‘an accident’ so that we must find meaning where we can. His characters seem to find that meaning outside fictive realism in a mystical equanimity discovered only through a personal retreat and silence that is at odds with the contemporary world and its attitudes. This paper seeks to explore that process as presented in Malouf's prose and poetry.